Polypyrrole-reduced graphene oxide coated delignified wood for highly efficient solar interfacial steam generation. (25th January 2023) - Wong, M.Y.; Zhu, Y.; Ho, T.C.; Pan, A.; Tso, C.Y.
Graphical abstract: Highlights: A highly efficient interfacial steam generator is fabricated. Transient heat transfer model is developed to evaluate the evaporation performance. A trade-off between polypyrrole and reduced graphene oxide content is observed. The maximum solar-to-vapor conversion efficiency of 93% is obtained experimentally. Abstract: A solar interfacial steam generator is a device that localizes the solar energy at the water–air interface for water evaporation. The solar interfacial steam generator can be applied in various evaporation-based thermal systems to enhance system efficiency by reducing heat dissipation. In this study, a bio-inspired polypyrrole-reduced graphene oxide coated wood was fabricated and investigated for evaporation and solar-to-vapor conversion efficiency improvement with different polypyrrole-reduced graphene oxide ratios. Thanks to the synergistic effect of highly solar-absorbed polypyrrole and water-attracted reduced graphene oxide, and the efficient heat transfer two-dimensional pathway, the polypyrrole-reduced graphene oxide coated wood showed an outstanding water evaporation performance. The highest water evaporation rate obtained by the polypyrrole-reduced graphene oxide coated wood with the reduced graphene oxide content of 60 % was 1.49 kg·m −2 ·hr -1, showing a nearly 10 % and 19 % improvement compared to polypyrrole and reduced graphene oxide coated woods, respectively. The corresponding solar-to-vapor conversion efficiency (93.1 %) was also beyond most of the wood-based interfacial steam generators in the literature. The transient heat transfer and evaporation performances of the polypyrrole-reduced graphene oxide coated wood were also firstly investigated based on the developed transient models. It is expected that the remarkable results of this study can help to promote and facilitate the study and application of interfacial steam generators in various thermal systems.